Kidney Response to Chemotherapy-Induced Heart Failure: mRNA Analysis in Normotensive and Ren-2 Transgenic Hypertensive Rats - Jíchová, Šárka; Gawryś, Olga; Kompanowska-Jezierska, Elżbieta; Sadowski, Janusz; Melenovský, Vojtěch; Hošková, Lenka; Červenka, Luděk; Kala, Petr; Veselka, Josef; Čertíková Chábová, Věra (International journal of molecular sciences, 2021)
The aim of the present study was to perform kidney messenger ribonucleic acid (mRNA) analysis in normotensive, Hannover Sprague-Dawley (HanSD) rats and hypertensive, Ren-2 renin transgenic rats (TGR) after doxorubicin-induced heart failure (HF) with specific focus on genes that are implicated in the pathophysiology of HF-associated cardiorenal syndrome. We found that in both strains renin and angiotensin-converting enzyme mRNA expressions were upregulated indicating that the vasoconstrictor axis of the renin-angiotensin system was activated. We found that pre-proendothelin-1, endothelin-converting enzyme type 1 and endothelin type A receptor mRNA expressions were upregulated in HanSD rats, but not in TGR, suggesting the activation of endothelin system in HanSD rats, but not in TGR. We found that mRNA expression of cytochrome P-450 subfamily 2C23 was downregulated in TGR and not in HanSD rats, suggesting the deficiency in the intrarenal cytochrome P450-dependent pathway of arachidonic acid metabolism in TGR. These results should be the basis for future studies evaluating the pathophysiology of cardiorenal syndrome secondary to chemotherapy-induced HF in order to potentially develop new therapeutic approaches.
Keywords: nemoci ledvin; Animals; Doxorubicin; Kidney; hypertenze; Female; protinádorová antibiotika; ženské pohlaví; Heart Failure; Renin; srdeční selhání; renin-angiotensin systém; Renin-Angiotensin System; messenger RNA; Antibiotics, Antineoplastic; Kidney Diseases; Rats, Sprague-Dawley; RNA, Messenger; regulace genové exprese; Hypertension; Male; potkani Sprague-Dawley; Rats, Transgenic; doxorubicin; krysa rodu Rattus; Gene Expression Regulation; zvířata; mužské pohlaví; ledviny; renin; Rats; potkani transgenní